Nuanced understandings of privatization in local authorities' services to schools. (January 2015) - Boyask, Ruth
This article draws upon findings from the New Relations between Local Authorities (LAs) and Schools project to identify ideological and value-based differences between the models of service to schools adopted within four case study LAs. While each of the LAs has developed a privatized model of service, there are subtle differences between the models, which I term cooperative, entrepreneurial, community engagement and corporate. In this article I describe the differences between these models, and their underpinning values.